The sinister way : the divine and the demonic in Chinese religious culture - Von Glahn, Richard (University of California Press, 2004)
In 'The Sinister Way', Richard von Glahn examines the emergence and evolution of the Wutong cult within the larger framework of the historical development of Chinese popular or vernacular religion - as opposed to institutional religions such as Buddhism or Daoism.